Brain volume loss and no evidence of disease activity over 3 years in multiple sclerosis patients under interferon beta 1a subcutaneous treatment. (January 2019) - Rojas, J.I.; Sanchez, F.; Caro, F.; Miguez, J.; Patrucco, L.; Funes, J.; Cristiano, E.
Highlights: The objective was compare the annual rate of brain volume loss (aBVL) in patients with RRMS according to NEDA status. 87 patients, mean age 33 ± 6 years were included, all patients received IFN beta 1a as MS treatment. aBVL from baseline to months 24 in NEDA patients was −1.1% vs. −1.54% in patients without NEDA (p < 0.001). From baseline to month 36 it was −1.43% vs. −2.1% (p < 0.001) in patients with and without NEDA, respectively. At 3 years follow up, patients who were disease-free had lower aBVL compared to patients with disease activity. Abstract: The objective of our study was to evaluate the relationship of percentage of annualized brain volume loss (aBVL) and no evidence of disease activity (NEDA) in multiple sclerosis (MS) patients under interferon beta 1-a subcutaneous treatment (IFN-beta) during 3 years of follow up. Relapsing remitting MS (RRMS) patients, with less than three years from disease onset, expanded disability status scale (EDSS) ≤3 and in which IFN beta 1-a 44 mcg was indicated, were included. Demographic, clinical and structural parameters from the magnetic resonance (MR) during the 3 years of follow up were analyzed and compared between patients with and without NEDA (defined as the absence of: (a) three-month confirmed disability progression defined as an increase in EDSS score of 1.0; (b) confirmed relapses; and (c) new or enlarged T2 lesions and/or Gd+ lesions). A total of 87 patients, mean age 33 ± 6 years were included. NEDA was reached by 39 patients at year 3. Percentage of aBVL from baseline to months 24 in NEDA patients was −1.1% vs. −1.54% in patients without NEDA (p < 0.001) and from baseline to month 36 it was −1.43% vs. −2.1% (p < 0.001) in patients with and without NEDA, respectively. At 3 years follow up, patients who received IFN beta 1a and were disease-free had lower percentage of aBVL compared to patients with disease activity.